Effect of health education on breastfeeding initiation techniques among postnatal mothers admitted in a tertiary care centre of Raipur city, Chhattisgarh - Gupta, Shubhra Agrawal; Sharma, Mini; Ekka, Abha; Verma, Nirmal (International Journal Of Community Medicine And Public Health, 2018)
Background: The health benefits of breastfeeding are well documented in public health and medical literature worldwide. It is reported in various studies that early lactation supported by correction of positioning and attachment of breastfeeding improves the rate of effective suckling. However, related to breastfeeding technique, no studies were conducted in Chhattisgarh, Therefore, this study was undertaken to assess the improvement in breastfeeding technique (positioning & attachment) after intervention(health education and support) among mother-early neonate units admitted in postnatal ward immediately after delivery in a tertiary level health institute. Methods: A Quasi-experimental (Single group pre and post design) carried out in hospital settings from August to September 2014. This study involved 414 both preterm and term babies who were born during the study period at Dr. BRAM hospital, Raipur with their mothers.Mothers were observed for breast feeding technique on first day followed by correction and post interventional observation. Results: After intervention statistically significant improvement was seen in overall body positioning status and attachment during breast feeding 43.3%, 42.1% respectively. Conclusions: Present study indicate that educating and supporting the mothers regarding correct breastfeeding technique is important to help them in the stage when they are establishing breastfeeding. This also avoids early and late problems related to breastfeeding.